2021
DOI: 10.3390/nursrep11010018
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Provider Attitudes toward the Newly Developed COVID-19 Vaccine: Cross-Sectional Study

Abstract: Background: During the long wait and the global anxiety for a vaccine against COVID-19, impressively high-safety and effective vaccines were invented by multiple pharmaceutical companies. Aim: We aimed to assess the attitudes of healthcare providers and evaluate their intention to advocate for the vaccine. Methods: This was a cross-sectional study conducted in a tertiary private hospital where an electronic survey was distributed among healthcare providers (HCPs). The survey contained two sections: socio-demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…Another variable shown to affect attitude toward vaccination uptake was age. Given this, older age was found to have a significant association with a positive attitude against COVID-19 vaccination in studies reported from Belgium, 35 Canada, 38 France, 41 Greece, 45 the USA, 15 , 40 ,Saudi Arabia, 39 Arabic-speaking countries, 37 and Slovenia. 34 Conversely, a report from Italy 44 exhibited associations between younger age (<30 years) and positive attitude toward vaccination.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Another variable shown to affect attitude toward vaccination uptake was age. Given this, older age was found to have a significant association with a positive attitude against COVID-19 vaccination in studies reported from Belgium, 35 Canada, 38 France, 41 Greece, 45 the USA, 15 , 40 ,Saudi Arabia, 39 Arabic-speaking countries, 37 and Slovenia. 34 Conversely, a report from Italy 44 exhibited associations between younger age (<30 years) and positive attitude toward vaccination.…”
Section: Resultsmentioning
confidence: 93%
“…Sex was observed to influence the attitude of healthcare workers against COVID-19 vaccination, with males demonstrating a lower anti-vaccination approach or positive attitude in the sample of studies reported from seven countries (7/24=29.2%) and females showing only in two studies reported from Ghana 49 and Saudi Arabia. 39 In contrast, more negative attitudes against COVID-19 were observed among female healthcare workers as evidenced from the surveys carried out in the USA, 15 Arabic-speaking countries, 42 Israel, 43 and Ghana. 49 …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations